2006
DOI: 10.1074/jbc.r500018200
|View full text |Cite
|
Sign up to set email alerts
|

Protamines, in the Footsteps of Linker Histone Evolution

Abstract: It was perhaps a lucky coincidence that the early attempts to establish the chemical composition of the cell nucleus were initially carried out on such diverse biological systems as salmon sperm heads (1) and geese and chicken erythrocytes (2). Examination of sperm and erythrocyte systems, respectively, lead to the protamine and histone concepts (3). We know with certainty that, with the exception of the male gametes, all somatic cells exclusively contain histones. Hence, in metazoans, protamines (4, 5) are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 55 publications
1
56
0
1
Order By: Relevance
“…This is especially evident in mammals where 11 different linker histones have been identified (see (13) for review). In contrast to core histones, whose origin can be traced back to archaebacteria, (37) the evolutionary origin of histone H1 appears to have occurred early in eubacteria.…”
Section: The Organization Of Sperm Chromatinmentioning
confidence: 92%
See 1 more Smart Citation
“…This is especially evident in mammals where 11 different linker histones have been identified (see (13) for review). In contrast to core histones, whose origin can be traced back to archaebacteria, (37) the evolutionary origin of histone H1 appears to have occurred early in eubacteria.…”
Section: The Organization Of Sperm Chromatinmentioning
confidence: 92%
“…(10,11) The term ''protamine-like'' was first described by Subirana. (12) The PL-type of SNBPs represent a structurally and functionally intermediate group between the H-and P-type SNBPs that are related to histone H1 (1,13,14) (Fig. 1A, B).…”
mentioning
confidence: 98%
“…Mitochondrial DNA (mtDNA) can form nucleoids with structure similar to chromatin in plants (13), and the yeast literature has demonstrated that histone family proteins are important in proper mitochondrial function (7,9,11). There are also evolutionary correlates of histone-like proteins that are important in DNA structure in the prokaryotic organisms that are thought to represent the predecessors of mitochondria (15,19,22). The electron micrographs of the mitochondrial nucleoid demonstrate a tightly wound ball of DNA (13) with protein associated, whereas proteins similar to the yeast histone HM protein have been isolated in bovine heart mitochondrial preparations (34).…”
Section: Discussionmentioning
confidence: 99%
“…5A). In C7, the AT-hooks are replaced by the 102-residue, R-rich human protamine 2 (Prt2; theoretical pI ϭ 11.9), which lacks a defined structure and binds DNA in vitro like H1 CTR but with higher affinity (27,28). In C8, the AT-hooks are replaced by the 105-residue human cytochrome C (CytC; theoretical pI ϭ 9.58), which has defined structure and can bind DNA because of its positive charge although it is not a proper DNAbinding protein (29).…”
Section: Card Chimeras Containing the Cardad C-terminal Segment Functmentioning
confidence: 99%